XALQONA QASAMLARDA FONATSION VOSITALAR («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Oath, which is one of the genres of speech, is one of the genres of the speech genre, folk oaths. The folk oath text is distinguished from other types of oaths by its emotional expressiveness.
Keywords: Intonation, accent, speech melody, pause, neutral intonation.